The Influences of Heat Stress on Rumen Functions - Rahmati, Shahpoor (Journal of Natural Sciences – Kabul University, 2021)
The livestock sector is evolving in response to the rapidly increasing demand for livestock products. The ruminant population is a primary driver of the growth of the livestock sector, alongside pigs and poultry. An increase in environmental temperature negatively impacts the basic physiology of the rumen, which affects production. Dry matter intake begins to decline as an adaptive response to heat stress. Increased environmental temperatures reduce gut motility, rumination, ruminal contractions, and suppress appetite in ruminants. Heat stress also reduces the total production of volatile fatty acids (VFA), with individual variations, and alters ruminal pH. Changes in microbiota due to heat stress may modify fermentation patterns in the rumen, resulting in variations in digestibility, VFA production, and methane emissions. This study aims to review the effects of heat stress on rumen functions in adult cattle, heifers, and calves.